1996
DOI: 10.1007/bf01275444
|View full text |Cite
|
Sign up to set email alerts
|

Efficient transgenic plant regeneration throughAgrobacterium-mediated transformation of Chickpea (Cicer arietinum L.)

Abstract: Three genotypes of chickpea ICCV-1, ICCV-6 and a Desi (local) variety were tested for plant regeneration through multiple shoot production. The embryo axis was removed from mature seeds, the root meristem and the shoot apex were discarded. These explants were cultured on medium containing MS macro salts, 4X MS micro salts, I35 vitamins, 3.0 mg/1 BAP, 0.004 mg/1 NAA, 3% (w/v) sucrose and incubated at 26(0)C. The explants were transformed withAgrobacterium tumefaciens strain LBA4404 with binary vector pBI121 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Direct shoot organogenesis and establishment of plantlets from different explants of chickpea was reported earlier (Polisetty et al, 1996(Polisetty et al, , 1997Paul et al, 2000;Rizvi and Singh, 2000;Chauhan et al, 2003;Jayanand et al, 2003;Chakraborti et al, 2006). Plantlets were developed through direct somatic embryogenesis and through callus from different explants of chickpea (Barna and Wakhlu, 1993;Sagare et al, 1993;Suhasini et al, 1994;Kumar et al, 1994Kumar et al, , 1995Rizvi and Singh, 2000;Chauhan et al, 2002;Kar et al, 1996Kar et al, , 1997Kiran et al, 2005).…”
Section: Introductionmentioning
confidence: 74%
“…Direct shoot organogenesis and establishment of plantlets from different explants of chickpea was reported earlier (Polisetty et al, 1996(Polisetty et al, , 1997Paul et al, 2000;Rizvi and Singh, 2000;Chauhan et al, 2003;Jayanand et al, 2003;Chakraborti et al, 2006). Plantlets were developed through direct somatic embryogenesis and through callus from different explants of chickpea (Barna and Wakhlu, 1993;Sagare et al, 1993;Suhasini et al, 1994;Kumar et al, 1994Kumar et al, , 1995Rizvi and Singh, 2000;Chauhan et al, 2002;Kar et al, 1996Kar et al, , 1997Kiran et al, 2005).…”
Section: Introductionmentioning
confidence: 74%
“…Three-to 4-week-old calli and excised embryo-axes from 3 to 4-d-old germinated immature seeds exhibited great regeneration potential, which subsequently declines with increasing age of the target cells. We have clearly demonstrated that tissues which respond well in tissue culture, also tended to respond well In most of the previous reports on Agrobacteriummediated transformation of chickpea, either embryo axes or slices of embryo axes were used as the target tissue (Fontana et al 1993, Kar et al 1996, Krishnamurthy et al 2000, Polowick et al 2004, Senthil et al 2004) and two of the recent reports were based on the decapitated embryo explant attached with one half of the cotyledon (Sarmah et al 2004, Tewari-Singh et al 2004. However, in the present study, one-month-old, dark-green cotyledonary-node-derived calli showed the highest transformation efficiency and was found to be the best source of explant for regeneration of complete plant from all the four genotypes compared to any other source of explants used.…”
Section: Discussionmentioning
confidence: 94%
“…For example, Fontana et al (1993) claimed a 4 % success rate to achieve only 3 GUS positive transgenic chickpea plants. Kar et al (1996), Krishnamurthy et al (2000) and Tewari-Singh et al (2004) reported Agrobacterium-mediated transformation of chickpea based on multiple shoot formation from embryo axis explants. Only Krishnamurthy et al (2000) and Tewari-Singh et al (2004) reported the inheritance of transgene in T 1 generation of transformed plants of chickpea.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, there are limited reports of reliable rooting and establishment of in vitro regenerated shoots in soil. Probably due to these difficulties the genetic transformation of chickpea (Fontana et al 1993;Kar et al 1996;Polowick et al 2004;Senthil et al 2004) has not made any significant progress as of now. The few reports so far published by independent research groups on transgenic chickpea plants for developing resistance against either pod borer or storage pests, were using particle bombardment or Agrobacterium-mediated transformation technique (Kar et al 1997;Sarmah et al 2004;Sanyal et al 2005;Indurker et al 2007).…”
Section: Discussionmentioning
confidence: 97%